GENERALIZED ANALYSIS OF HARMONIC DISTORTION IN THE D-TCSC - e Silva, Luciano S. C.; Seixas, Falcondes J. M. de [UNESP]; Junior, Dionizio P. [UNESP]; Junior, Joao C. P. [UNESP]; Resende, Jose F.; Garcia, Henrique L.; IEEE (Ieee, 2015)
The objective of this work is to present a generalized analysis of power quality of the Thyristor Controlled Series Compensator for electrical distribution systems application (D-TCSC). The studies include normalized graphics that indicate the harmonic behavior and the possibilities of parallel resonance of D-TCSC. The main simulation results show the improvement of the voltage load and confirm the behavior of the normalized graphics that are presented in comparative Tables.
Keywords: D-TCSC; Harmonics; Distribution Systems